Under Duress or Coercion. Special Land Registry Cancellation Lawsuits after the Second Vienna Award - László Ádám Joó (Journal on European History of Law)
Following the Second Vienna Award, in possession of the general authorisation of the Parliament, the Hungarian Royal Government adopted several decrees in order to extend the scope of Hungarian private law to the regions concerned. At first the scope of the law of real estate was extended by Decree No. 1440/1941. In Section 6 the legislator provided the right for those who alienated their immovable properties during the period of the Romanian supremacy to request in integrum restitutio, in a measure through the deletion of the current owner’s right of ownership. The court could also uphold the application if the transaction concluded under a compulsive action of a Romanian authority threatening with damage and serving the interests of the party that acquired the right or other official direct or indirect coercion or the threat of procuring it. After the analysis of the available judgments found in the Hungarian National Archives, it is ascertainable that the courts did not interpret the above-mentioned conditions consistently, therefore they could not always choose the appropriate one of them. Despite that, cancellation from land registry was ordered in most cases in which the owner was forced to alienate his/her immovable property under some kind of duress or coercion of an authority. Although the Decree was in force until the Romanian reoccupation and the system of private property was altered extremely in the communist regime, the lessons of the judicial practice of the discussed decree should get attention.